Pengaruh Ultrasound Diathermy dan Latihan Pendulum Terhadap Pengurangan Nyeri pada Bursitis Bahu di Instansi Rehabilitasi Medik RSUD dr. Saiful Anwar Malang - Najakhul Imtikhani; wiek Israwan; Amin Zakaria; Fransisca Xaveria Hargiani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:     To prove a decrease in pain scale in shoulder bursitis pain by giving a combination of diathermy ultrasound treatment with codman's pendulum exercise.Methods:  The design of this study used the Quasi Experimental pre test and post test one group method with no control group. The number of samples as many as 20 men and women aged between 40 to 65 years old with purpose sampling technique were given diathermy ultrasound treatment and pendulum exercise 8 times for 4 weeks. The pain scale test uses the visual analogue scale (VAS) while the functional ability test uses the shoulder pain and disability index (SPADI). The data were analyzed using the statistical package for the social sciences (SPSS) program. Normality test using shapiro wilk statistical test. Results:   The results showed that pre 0.183>0.05 was normally distributed, the post value was 0.404>0.05, meaning that it was normally distributed. Testing the hypothesis using the Paired Sample t-test statistical test with a significance value of 0.000 <α 0.05, so it can be concluded that there is a significant difference in shoulder bursitis pain before and after being given diathermy ultrasound treatment and codman’s pendulum exercise.Conclusion:   This study indicate that the intervention of ultrasound diathermy and codman’s pendulum exercise has an effect on reducing pain in shoulder bursitis and functional ability of the shoulder.